A Systematic Review of the Effectiveness of Acceptance and Commitment Therapy for Managing Grief Experienced by Bereaved Spouses or Partners of Adults Who Had Received Palliative Care. (October 2022) - Jones, K.; Methley, A.; Boyle, G.; Garcia, R.; Vseteckova, J.
This systematic review investigated the effectiveness of Acceptance and Commitment Therapy (ACT) for managing grief experienced by bereaved spouses or partners of adults who had received palliative care. Systematic searches were undertaken on seven bibliographic databases and grey literature was also searched. The review was informed by the use of the PICO framework and PRISMA-P guidelines. Initially 30 relevant papers were identified, but only two international studies met the criteria for inclusion. One was a qualitative, doctoral study using Interpretative Phenomenological Analysis; the other, a randomized controlled trial comparing ACT with usual psychosocial support. These studies showed some evidence of benefit for bereaved individuals, particularly by promoting the acceptance of troubling emotions. However, this type of therapy may be more effective in reducing psychological distress rather than grief. Further research is needed into the value of ACT in addressing grief following bereavement.